Mental health problems among transition-aged youth with physical disabilities: an initial evaluation - Amalfi, Amanda; Li, Jia Yin; Théberge-Lamoureux, Vanessa; Tang, Carmen; Rinaldi, Emilie; Khayargoli, Pranamika; Anaby, Dana (Frontiers in Rehabilitation Sciences, 2023)
Aim: Decreased participation and complex transitions into adulthood among youth with disabilities may impede their well-being. To advance knowledge on the co-occurrence of mental health problems and physical disability, this brief report describes the frequency of mental health problems, measured by the Behavior Assessment System of Children (BASC-3), among transition-aged youth (14-25 years) with physical disabilities and examines the association between mental health problems and sex, age, and number of functional issues. Methods: Thirty-three participants completed a demographic questionnaire and the BASC-3. Frequency of BASC-3 scales falling within 3 categories: ‘within norms’, ‘at risk’, and ‘clinically significant’ were described. Crosstabs and Chi-square tests were used to examine the association between BASC-3 scales and sex, age (< and ≥ 20), and number of functional issues (< and ≥ 6). Results: Overall, ‘somatization’, ‘self-esteem’, ‘depression’ and ‘sense of inadequacy’ were the most common subscales being at risk. Participants with a higher number of functional issues (≥6) were more likely to fall within ‘at risk’ or ‘clinically significant’ categories across 20 (out of 22) BASC-3 scales, and female participants tended to fall more within ’at risk’ or ‘clinically significant’ categories for 8 of BASC-3 scales. Younger participants (<20) were ranked in the ‘at risk’ or ‘clinically significant’ categories for 7 scales. Conclusions: Findings lend further support for the occurrence of mental health problems emerging in youth with physical disabilities and highlight initial trends especially across functional levels. Further investigation of such co-occurrences and the factors that affect their development is needed.